A study of steroid-sensitive nephrotic syndrome among children attending nephrotic clinic of tertiary care hospital of North Gujarat - Dalal, Ekta; Upadhyay, Nisha Chintan (Indian Journal of Child Health, 2019)
Introduction: Nephrotic syndrome (NS) is an important chronic disease in children. About 80% of children with idiopathic NS show remission of proteinuria following treatment with corticosteroids and are classified as “steroid sensitive (SS).” Most patients have multiple relapses, placing them at risk for steroid toxicity, systemic infections, and other complications. Objective: The objective of the study was to determine the rate of steroid responsiveness in children with NS admitted to children’s ward with classical idiopathic NS and also to study the long-term complications of high-dose steroid therapy. Materials and Methods: This prospective study was conducted from April 2016 to March 2018 (including 1 year follow-up period) in the pediatric ward of tertiary care hospital. Children with SSNS aged 6 months–10 years were included in the study. The demographic, clinical, laboratory data, response to various therapies, and 1-year follow-up data were collected. Data were captured and analyzed using Microsoft Excel software. Results: A total of 102 SSNS children were studied. The disease course at 1 year was categorized as non-relapse (38.2%), infrequent relapse (38.2%), frequent relapse (23.2%), and steroid dependent (14.7%). The major presenting symptoms were edema (100%), burning micturition (52%), and fever (44%) while the major presenting sign was anasarca. A total of 57.8% of the patients were presented with the first attack and the remaining 42.2% of patients presented in relapse. Acute kidney injury was observed in 14.29% of cases. Infections were the most common complication of NS. All the children were treated with standard guidelines given by the Indian Academy of Pediatrics nephrology group. 12% of patients with frequent relapse and 8% of patients with steroid-dependent NS were treated with long-term low-dose steroid. Remaining non-responsive patients had either levamisole or cyclophosphamide added to their treatment regimen. Cushingoid features (44.9%) were the most common side effect followed by hypertension (17.9%), gastrointestinal symptoms (6.7%), hyperglycemia (4.5%), infection 18%, and growth retardation (4.9%). Conclusions: A high proportion of patients with SSNS shows frequent relapse, risk factor for which was an early age at onset, inadequate initial therapy, and early relapse.